Analisis Jenis, Faktor dan Solusi dari Kesulitan Guru Dalam Mengimplementasikan Pembelajaran Tematik SD: Penelitian - Mahesty, Naeny; Salfina Damayanti; Naila Bintang Titania Putri Riyadi; Dea Amelia; Taufik Muhtarom (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The implementation of thematic learning in elementary schools still faces various obstacles that may hinder the achievement of educational goals. This research serves as the basis for a systematic review aimed at: (1) identifying the difficulties faced by teachers in implementing thematic learning in elementary schools; (2) understanding the factors that influence the difficulties faced by teachers in implementing thematic learning in elementary schools; and (3) finding solutions to the difficulties faced by teachers in implementing thematic learning in elementary schools. The research method employs a systematic literature review (SLR) approach with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data collection involved searching for relevant references on the topic through Google Scholar and Publish or Perish, resulting in 20 research articles (2015-2025). The data analysis technique used includes review techniques, peer interviews, and faculty guidance. Universally (1) teachers face difficulties at the stages of evaluation, planning, and implementation of learning, teacher understanding, and students with different characteristics and abilities; (2) factors causing difficulties for teachers in preparing lesson plans, low competence, limited resources, minimal training, and student abilities; (3) solutions applied include improving teacher capabilities, exchanging experiences, providing facilities and infrastructure, training, and conducting comparative studies.